SUBSTITUTION OF HIJAAN WITH WASTE MEDIUM MEDIA FERMENTATION WHITE FERMENTATION WITH NON KARKAS PERCENTAGE IN LOCAL SHEEP - Iin Dwi Lestari Silitonga; Hasnudi; Hamdan; T H Wahyuni; E R Mirwandhono (Jurnal Peternakan Integratif, 2017)
This study aims to determine whether the waste media plant white fermented oyster mushroom can substitute forage on sheep against non-carcass components are feasible eaten. This research was conducted in Namo Trasi Village, Pasar VIII, in October - December 2017 by using local sheep with average weight of 9 ± 0.25 kg. The research design used in this study was a complete randomized design (RAL) with 4 treatments and 5 replicates, consisting of P0 (60% non-wasted greenhouse vegetation fermentation + 40% concentrate), P1 (45% forage and waste) medium planting white oyster mushroom fermentation 15% + concentrate 40%), P2 (forage 30% and waste medium planting white oyster mushroom fermentation 30% + concentrate 40%) and P3 (forage 15% and sewage media plant white fermented oyster mushrooms 45% + 40% concentrate). The parameters observed were weight percentage of head, leg, skin, tail, trachea and lungs, liver, heart, blood, and gastrointestinal tract. The result of the research shows that the waste of fermented white oyster mushroom media can substitute forage as local sheep feed, but it can not increase the percentage of non-carcass component that is feasible to eat.